Organizational Culture-Based â€œAmongâ€ System Leadership Model in High School of Yogyakarta City - R. Purwanto, Hudi; Ekosiswoyo, Rasdi; Prihatin, Titi (Universitas Negeri Semarang, 2017)
The development of science, technology, and arts, as well as the development and social changes of a community, is so rapid. Thus, the challenge of the future education is not easy. Education is a cultural strategy and is not merely a conscious effort. As an educational institution, High School (SMA) has a very strategic role to restore education to the spirit and identity of Indonesia. The principal has a very important role to play in his/her vision and mission, and the school's organizational culture is an essential component of success in his/her leadership. The organizational culture-based â€œamongâ€ system leadership model is considered appropriate to be implemented by the principal. Therefore, it is necessary to further observe the leadership model and value system that is the organizational culture in the school. In general, this study aimed to describe the organizational culture-based â€œamongâ€ system leadership model in five public and private multicultural high schools, and those which are religiously affiliated in the city of Yogyakarta. The five schools include SMA Negeri 3, Taman Madya Tamansiswa High School, SMA PIRI I (Islam), Christian BOPKRI I High School, and Catholic Marsudi Luhur High School, all of which are in Yogyakarta City. This study employed a qualitative approach with data from the natural background as the source of primary data. This study aims to know and simultaneously describe the leadership model of the organizational culture-based â€œamongâ€ system of the schools in Yogyakarta City. The study was designed as a multi-case study model. To be able to understand the meaning of such events and interactions, theoretical orientation and theoretical perspective with a phenomenological approach were employed. Based on the results of the documentary, observation, and interviews studies, this study shows differences between the five high schools although nuances to Indonesia is in fact still reflected in it. The differences can be interpreted as a diversity that is a reflection of the specificity and typicality of the schools concerned. Besides, it was found that the organizational culture was developed on the basis of local wisdom, nationalism, and Islamic faith. It is these factors that affect the leadership pattern of the principals in the schools. The fact shows that the leadership model implemented in the High Schools in Yogyakarta City dominantly refers to government regulation and or foundation one for the private schools; it also has a multicultural nuance based on the local or religious wisdom or a combination of both. It is implemented with the slogans of silih asih, asuh, and asah which are actually the essence of â€œamongâ€ system leadership model. Islamic schools need to go deeper into the wisdom of Rasulullah Muhammad S.A.W's leadership, known as prophetic leadership, to act as worship, to give priority to ministry, instead of asking to be served. The prominent Christian teaching is the spirit of loving that is based on service which needs a profound interpretation that love is giving rather than asking for services. Therefore, the organizational culture-based among system leadership model of the schools that refers to local, national, and religious wisdom is expected to produce an optimal and sustainable performance.